2009
DOI: 10.3233/jrs-2009-0454
|View full text |Cite
|
Sign up to set email alerts
|

Quality and safety considerations for recombinant biological medicines: A regulatory perspective

Abstract: Biological medicines have introduced a new set of quality and safety issues because these medicinal products are large molecules synthesized in complex biological processes and may have pharmacodynamic properties that need extra consideration and study for safe administration to humans. A complex manufacturing process and molecular structure means that the exact identity of the material cannot be guaranteed by analytical technology alone but requires a well understood and reproducible manufacturing process. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Manufacturers of originator products use proprietary growth and purification conditions and specially adapted cell lines for their processes; therefore, knowledge of the protein sequence or cells used by the originator is not sufficient for a biosimilar sponsor to produce the same biologic product. Differences in structure between proposed biosimilar and reference product need to be minimized because even subtle differences can potentially affect PK, efficacy, safety, and immunogenicity [ 16 18 ].…”
Section: Development Of Biosimilarsmentioning
confidence: 99%
“…Manufacturers of originator products use proprietary growth and purification conditions and specially adapted cell lines for their processes; therefore, knowledge of the protein sequence or cells used by the originator is not sufficient for a biosimilar sponsor to produce the same biologic product. Differences in structure between proposed biosimilar and reference product need to be minimized because even subtle differences can potentially affect PK, efficacy, safety, and immunogenicity [ 16 18 ].…”
Section: Development Of Biosimilarsmentioning
confidence: 99%
“…These minor differences between a proposed biosimilar and the reference product can influence the pharmacologic profile, efficacy, safety and immunogenicity and therefore must be carefully identified and quantified at the outset. [11][12][13] Another important consideration in developing biosimilars is to understand the difference between comparability and biosimilarity. Comparability refers specifically to the assessment of characteristics of the biologic product after a specific change is made to the manufacturing process by the manufacturer of the product.…”
Section: Development Of Biosimilars: Analytical Preclinical and Clinmentioning
confidence: 99%
“…Mutations in the cell line also may contribute to minor sequence variants. These minor differences between a proposed biosimilar and the reference product can influence the pharmacologic profile, efficacy, safety and immunogenicity and therefore must be carefully identified and quantified at the outset …”
Section: Development Of Biosimilars: Analytical Preclinical and Clinmentioning
confidence: 99%
“…It was found that 3 years after their marketing approval, 14% of medicines are subject to interventions, a figure that increases to 29% after 10 years [57]. Moreover, the first medicines belonging to a new therapeutic class are associated with an increased prevalence of adverse events [60].…”
Section: Risk and Traceabilitymentioning
confidence: 99%